Cabin Fever During Isolation Due to Covid-19: What Should We Do to Overcome it? - Nurhadi, Grace Manuela; Alya Shafira Hewiz; Jihan Nabila Pranjasdhina; Fiqih Faizara Ustadi; Fathiya Rahma Hermawan; Almira Maharani; Alfira Nailatul Izzah; Muhammad Khafidin Al Alim; Danty Puspitasari; Yunias Setiawati (Faculty of Medicine, Universitas Airlangga, 2024)
Introduction: Cabin fever is described as some combination of irritability, moodiness, and depression due to isolation during COVID-19. Cabin fever may happen to anyone who has to isolate themself at home because of the COVID-19 outbreak. We aim to identify the risk factor, the influence of hormone imbalance on mood changes, and how to deal with cabin fever during isolation due to COVID-19. People who are unable to connect with other people physically, unable to do activities that they used to do, unmotivated due to having no work, and anxious about finances due to lack of income may have a higher risk of cabin fever. Review: Social isolation experienced by people with cabin fever may result in hormonal imbalances that eventually affect their mood. This is due to the stress that comes from prolonged stay-at-home orders, which are thought to disturb the balance of the hormones in a person’s body. Hormones which are able to cause mood changes are cortisol, thyroid, testosterone, estradiol, and progesterone. Cabin fever is not a recognized psychological condition. In this way, there is no standard treatment for cabin fever. Conclusion: Therefore, acceptance, reconciliation with oneself, coexistence and trust (intimate interactions, mindfulness, and positive self-shaping as self-control) are keys to overcome cabin fever.